A general method for retrieving thermal deformation properties of microencapsulated phase change materials or other particulate inclusions in cementitious composites. (15th July 2017) - Young, Benjamin A.; Wei, Zhenhua; Rubalcava-Cruz, Jose; Falzone, Gabriel; Kumar, Aditya; Neithalath, Narayanan; Sant, Gaurav; Pilon, Laurent
Abstract: This study examined the effects of spherical core-shell particle inclusions, such as microencapsulated phase change materials (PCMs), on the thermal deformation behavior of cement-based composites. First, simulations of volumetric thermal deformation in representative microstructures were carried out, based on the finite element method (FEM), to predict the effective thermal deformation coefficient of the composites. Excellent agreement was found between the effective thermal deformation coefficient predicted by FEM and by the effective medium approximation (EMA) developed by Schapery (1968). Furthermore, the effective thermal deformation coefficient of cementitious composites with either microencapsulated PCM or quartz particulates was measured. The measured effective thermal deformation coefficients together with Schapery's model were used to retrieve the thermal deformation coefficients of the inclusions themselves. The thermal deformation coefficient of PCM microcapsules was estimated to be similar to that of the shell component due to partial filling of the microcapsules. The results show a means for (i) retrieving the thermal deformation properties of functional core-shell inclusions and (ii) for designing cementitious composites with PCMs which find use in the built environment and high-performance composites. Graphical Abstract: Highlights: A general method to retrieve material properties of particulate inclusions in composite materials was outlined. The effective thermal deformation coefficient of composites containing core-shell inclusions was predicted with rigorous finite element simulations. Excellent agreement was found between Schapery's model and the numerically predicted effective thermal deformation coefficient. The effective thermal deformation coefficient of cement paste with various volume fractions of microencapsulated PCM and/or quartz inclusions was measured. The thermal deformation coefficient of PCM microcapsules was retrieved by fitting Schapery's model to the experimental measurements.